PENGARUH CUSTOMER VALUE, PERCEIVED QUALITY, DAN TRUST IN BRAND TERHADAP BRAND LOYALTY PADA PRODUK INDOMIE (Studi Kasus pada Mahasiswa S1 Universitas Diponegoro Semarang) - Errisa Dila Ayunda; Naili Farida (Universitas Diponegoro, 2018)
Indomie is an instant noodle brand that has become a market leader in Indonesia. The position occupied by Indomie now does not necessarily make Indomie guarantee its existence. If Indomie ignoring the presence of its competitors, it can disrupt the brand loyalty of Indomie. Indomie must be able to formulate the marketing strategy that can increase consumer trust so it can increase the brand loyalty of Indomie. This research aimed to determine the effect of customer value and perceived quality of the Indomie brand loyalty through trust in brand as an intervening variable. The type of the research is explanatory research, with a sample of 100 respondents who consume Indomie on student Undip through purposive sampling technique. The method of analysis used in this research was two steps regresstion analysis. The results showed that there are positive effect between customer value to trust in brand, and between perceived quality to trust in brand. Based on the two steps regression analysis showed that customer value and perceived quality has an effect of trust in brand. Next, trust in brand has an effect to brand loyalty. Suggestions of this research is to make innovation of instant noodle products that are more friendly to health. Make improvements in the quality control. And adjust the price of Indomie in order to compete with other instant noodle brand.